THE IMPORTANCE OF ERP SYSTEMS IN ENTERPRISES OF UZBEKISTAN - Jumaniyozova Mukaddas; Bakhronov Dilshod Baxtiyor o`g`li (Bright Mind Publishing, 2026)
This article examines the importance of ERP systems for enterprises in Uzbekistan in the context of the country’s ongoing digital transformation. The study analyzes how integrated information platforms enhance the efficiency of managing production, financial, logistics, and human resource processes. Special attention is given to the national strategy “Digital Uzbekistan – 2030,” which promotes large-scale adoption of digital solutions across public and private sectors. The findings show that the implementation of ERP systems contributes to cost optimization, improved transparency of operations, enhanced resource control, and the development of stronger competitive advantages for enterprises of different sizes.
Keywords: Digital technologies, ERP systems, government policy, types of systems, development coverage, business scale, ERP MADANIYAT, SAP, ORACLE.